2015
DOI: 10.1139/apnm-2014-0380
|View full text |Cite
|
Sign up to set email alerts
|

Cooking enhances beneficial effects of pea seed coat consumption on glucose tolerance, incretin, and pancreatic hormones in high-fat-diet–fed rats

Abstract: Pulses, including dried peas, are nutrient- and fibre-rich foods that improve glucose control in diabetic subjects compared with other fibre sources. We hypothesized feeding cooked pea seed coats to insulin-resistant rats would improve glucose tolerance by modifying gut responses to glucose and reducing stress on pancreatic islets. Glucose intolerance induced in male Sprague-Dawley rats with high-fat diet (HFD; 10% cellulose as fibre) was followed by 3 weeks of HFD with fibre (10%) provided by cellulose, raw-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
4
11
0
Order By: Relevance
“…Twenty-four hour food intake was also measured on two separate days throughout the four-week period. Body weight gain and food intake were comparable between groups as reported previously [ 6 ]. At the end of the study, rats were anesthetized with ketamine (100 mg/kg) and xylazine (1 mg/kg) and euthanized by exsanguination.…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…Twenty-four hour food intake was also measured on two separate days throughout the four-week period. Body weight gain and food intake were comparable between groups as reported previously [ 6 ]. At the end of the study, rats were anesthetized with ketamine (100 mg/kg) and xylazine (1 mg/kg) and euthanized by exsanguination.…”
Section: Methodssupporting
confidence: 85%
“…Dried peas ( Pisum sativum ) are one of the most common variety of pulses characterized as a rich source of dietary fiber. Peas and their components have been largely studied in terms of their favorable effects on glycemic control and insulin resistance as seen in prediabetes and T2D [ 2 , 3 , 4 , 5 , 6 ]. Most of these beneficial effects have been attributed to pea’s fermentable dietary fiber content and the consequent production of short chain fatty acids (SCFA).…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies have shown that legumes can reduce cardiovascular disease risk, and intervention studies suggest that this is mediated via improvements in blood pressure, lipid profile, inflammation, blood sugar metabolism and body weight 54,59 . Legumes also offer a food-based solution to decreasing risk of pre-diabetes 60 70 .…”
Section: Nutrition and Healthmentioning
confidence: 99%
“…We focused on the ability of EWH to alleviate insulin resistance, a key component of the MetS (32) . Prolonged HFD feeding is known to induce insulin resistance and glucose intolerance (29,33,34) , adipocyte dysfunction and inflammation (35,36) and dyslipidaemia (37,38) in rodents. Therefore, HFD-induced insulin-resistant Sprague-Dawley rats were chosen as the animal model.…”
Section: Discussionmentioning
confidence: 99%
“…The first trial was conducted to determine the effective dosage of the treatment, whereas the second trial further verified the effectiveness of the treatment as compared with the control group. In both trials, after 1-week of acclimatisation, all rats received a high-fat diet (HFD) (20 %, w/w) for 6 weeks to induce glucose intolerance as shown before (29) . Rats were then randomly assigned to one of the following groups: HFD, HFD+1 % EWH, HFD+2 % EWH and HFD+4 % EWH (n 7-8 each) in the first trial and to HFD and HFD+4 % EWH (n 7-8 each) in the second trial.…”
Section: Animals and Dietsmentioning
confidence: 99%